Intra cluster light properties in the CLASH-VLT cluster MACS J1206.2-0847 - Presotto, Valentina; Bartelmann, Matthias (Arxiv, 2014)
We aim at constraining the assembly history of clusters by studying the intra cluster light (ICL) properties, estimating its contribution to the fraction of baryons in stars, f*, and understanding possible systematics/bias using different ICL detection techniques. We developed an automated method, GALtoICL, based on the software GALAPAGOS to obtain a refined version of typical BCG+ICL maps. We applied this method to our test case MACS J1206.2-0847, a massive cluster located at z=0.44, that is part of the CLASH sample. Using deep multi-band SUBARU images, we extracted the surface brightness (SB) profile of the BCG+ICL and we studied the ICL morphology, color, and contribution to f* out to R500. We repeated the same analysis using a different definition of the ICL, SBlimit method, i.e. a SB cut-off level, to compare the results. The most peculiar feature of the ICL in MACS1206 is its asymmetric radial distribution, with an excess in the SE direction and extending towards the 2nd brightest cluster galaxy which is a Post Starburst galaxy. This suggests an interaction between the BCG and this galaxy that dates back to t <= 1.5 Gyr. The BCG+ICL stellar content is 8% of M_(*,500) and the (de-) projected baryon fraction in stars is f*=0.0177 (0.0116), in excellent agreement with recent results. The SBlimit method provides systematically higher ICL fractions and this effect is larger at lower SB limits. This is due to the light from the outer envelopes of member galaxies that contaminate the ICL. Though more time consuming, the GALtoICL method provides safer ICL detections that are almost free of this contamination. This is one of the few ICL study at redshift z > 0.3. At completion, the CLASH/VLT program will allow us to extend this analysis to a statistically significant cluster sample spanning a wide redshift range: 0.2<z<0.6.